Pengaruh Pendidikan Kesehatan Dengan Media Audio Visual Terhadap Peningkatan Motivasi Untuk Berhenti Merokok Pada Remaja Di SMAN "X" Banjarbaru - Dina Hanifa; Rachmawati, Kurnia; Setiawan, Herry (Nerspedia, 2023)
Background: Indonesia as a country with the highest number of adolescent smokers in the world. So to stopsmoking, it is necessary to be aware of the importance of health that can lead to motivation to quit smoking.Along with the development of the era of electronic media allows it as a medium in providing motivation,such as video. Objective: Determined the effect of health education with audio-visual media on increasingmotivation to quit smoking in adolescents at SMAN "X" Banjarbaru.